The role of regional innovation systems in cities Global regions - Caicedo Asprilla, Henry (Cuadernos de Administración, 2011)
This document is the result of a literature review of works trying to find the link between regional innovation systems and development of global city regions, and its purpose is to show that exist a complementarity between these two kinds of analysis and the relevance this has in the construction of regional policy and urban development. The analysis of the work on this pair of concepts warn the lack of a universally accepted definition of region is the main obstacle to integration into the regional political agendas, yet investigations show that spillovers, knowledgeintensive services and design of science and technology policy are the mechanisms through which knowledge and innovation are part of regional development. In this perspective it is concluded that global city regions such as New York, London, Tokyo, Madrid, Milan, Sydney, among others, are the main nodes of trade because they make intensive use of knowledge.